2017
DOI: 10.1159/000477593
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent CCR7 Overexpression and RelB Knockdown in Immature Dendritic Cells Induces Immune Tolerance and Improves Skin-Graft Survival in a Murine Model

Abstract: Background/Aims: Skin transplantation aims to cover skin defects but often fails due to immune rejection of the transplantated tissue. Immature dendritic cells (imDCs) induce immune tolerance but have a low migration rate. After stimulation, imDCs transform into mature DCs, which activate immune rejection. Thus, inducing imDC to obtain a high migration counteracts development of immune tolerance. Methods & Results: We transfected imDCs with a recombinant adenovirus carrying the CCR7 gene (Ad-CCR7) and a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Tregs play a significant role in inducing peripheral tolerance to self and foreign antigens [39]. As previously reported, the xenograft survival was longer in CD4+ T-cell-depleted mice, in contrast to in CD4+ T-cell mice [40]. In the current study, the results revealed increased expression of α-SMA in CCl 4 -induced hepatic fibrosis; however, the expression of desmin was found to be decreased.…”
Section: /Cd8supporting
confidence: 74%
“…Tregs play a significant role in inducing peripheral tolerance to self and foreign antigens [39]. As previously reported, the xenograft survival was longer in CD4+ T-cell-depleted mice, in contrast to in CD4+ T-cell mice [40]. In the current study, the results revealed increased expression of α-SMA in CCl 4 -induced hepatic fibrosis; however, the expression of desmin was found to be decreased.…”
Section: /Cd8supporting
confidence: 74%
“…C-C chemokine receptor 7 (CCR7), a G protein-coupled trans-membrane protein, can promote immune cell viability and induce immune cells homing to secondary lymphoid organs following cognate ligand binding like cytokines CCL19 and CCL21 [9, 10]. Whereas the exact roles of CCR7 in disease progression and in tumor metastasis to lymphoid tissues remain controversial so far.…”
Section: Introductionmentioning
confidence: 99%
“…The OS-RC-2 and 786-O cells were seeded on a 6-well plate and incubated with 50 nM siPGRMC1 or siNC per well. On the first day after siPGRMC1 treatment for RCC cells, cells were transfected with 2.5 µg pYR-ATP1A1 plasmids to further observe cell growth (31).…”
Section: Methodsmentioning
confidence: 99%